The effects of governance on institutional sustainability and outreach of the poor in microfinance institutions (MFIs) in Bangladesh - Hussain, Mohammad Delwar (School of Business Innovation & Technopreneurship, 2017)
This study concentrates on MFIs that were represent the frontier economic market such as data from a developing country, because poverty is prevalent in developing countries and microfinance working as a tool to reduce poverty. Therefore, it choses Bangladesh, as a mother country of microfinance, also poverty is prevalent in Bangladesh (UNDP, 2015). There are six hundred and ninety seven (697) MFIs under the microcredit regulatory authority in Bangladesh (MRA, 2015). However, based on data availability this study selects eighty (80) MFIs from Bangladesh. For collecting data this study relies on the MFI's official web site, annual reports, mix market rating reports, and most importantly, the annual financial statements.